2022
DOI: 10.3390/plants11212963
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Soil Matric Potential on the Germination Capacity of Prosopis chilensis, Quillaja saponaria and Cryptocarya alba from Contrasting Geographical Origins

Abstract: As a consequence of the megadrought in Central Chile, it is expected that most of the distribution of woody species will be narrowed in the northern limits because of restrictions imposed by soil matric potential on seed germination. In this study, we analyzed the effect of the soil matric potential on seed germination and initial recruitment of the sclerophyllous species Prosopis chilensis, Quillaja saponaria and Cryptocarya alba from contrasting geographic origins (i.e., seed sources). We evaluated the germi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 38 publications
(79 reference statements)
0
4
0
Order By: Relevance
“…The results suggest differences in the media conditions that favor the germination of both seeds. It has been reported that Q. saponaria seeds are highly affected by soil matric potential, with northern seed sources performing better under low soil matric potential [ 56 ]. For Pinus pinea seeds, it was observed that the germination is influenced by drought, salinity, and heat, with the highest germination percentage presented at 80 °C and short exposure time [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results suggest differences in the media conditions that favor the germination of both seeds. It has been reported that Q. saponaria seeds are highly affected by soil matric potential, with northern seed sources performing better under low soil matric potential [ 56 ]. For Pinus pinea seeds, it was observed that the germination is influenced by drought, salinity, and heat, with the highest germination percentage presented at 80 °C and short exposure time [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“… Topics in this Special Issue. Overview of topics and articles related to them: seed quality [ 1 , 2 ], physical and biological factors [ 3 , 4 ], seed pre-treatment [ 5 , 6 , 7 , 8 ], management [ 9 , 10 ], salt and drought stress [ 11 , 12 ], and seed technology [ 13 ]. …”
Section: Figurementioning
confidence: 99%
“…Arceo-Gómez et al [1] studied the seeds of Enterolobium cyclocarpum and Piscidia piscipula, Fabaceae tree species from the Yucatan Peninsula (Mexico). They used fresh physical and biological factors [3,4], seed pre-treatment [5][6][7][8], management [9,10], salt and drought stress [11,12], and seed technology [13].…”
Section: Seed Qualitymentioning
confidence: 99%
See 1 more Smart Citation